2022
DOI: 10.3389/fnut.2022.939714
|View full text |Cite
|
Sign up to set email alerts
|

Age-, sex-, and maturity-associated variation in the phase angle after adjusting for size in adolescents

Abstract: BackgroundApplied research using the phase angle (PhA) in children and adolescents has increased notably. Using multilevel modeling in a fully Bayesian framework, we examined the relationships between PhA, age, sex, biological maturity status, and body size in 10–16-year-old adolescents.MethodsThe sample comprised 519 adolescents (women, n = 241; men, n = 278) from Campinas, São Paulo, Brazil. Biological maturity status was assessed with self-examination of pubertal development for sexual maturity and maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In our study, after adjusting for multiple variables, logistic regression analysis confirmed that low PhA remained strongly associated with disability in hemodialysis patients, further expanding our understanding of the clinical value of PhA. Consistent with previous studies [ 36 38 ], our findings demonstrated that male subjects had higher PhA values. The sex difference in PhA might be associated with higher proportion of muscle and water in males, whereas female tend to have a higher proportion of body fat in females.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, after adjusting for multiple variables, logistic regression analysis confirmed that low PhA remained strongly associated with disability in hemodialysis patients, further expanding our understanding of the clinical value of PhA. Consistent with previous studies [ 36 38 ], our findings demonstrated that male subjects had higher PhA values. The sex difference in PhA might be associated with higher proportion of muscle and water in males, whereas female tend to have a higher proportion of body fat in females.…”
Section: Discussionsupporting
confidence: 91%
“…The justifications discussed in the literature are mainly based on the presence of greater muscle mass in males compared to females [ 23 ]. However, it is important to extrapolate to other factors, such as changes in body water, especially during the maturation period, and body size (height) [ 13 ]. Therefore, it is believed that it is important to consider sex-stratified analyses, which can help understand the differences in physical growth, body composition, and lifestyle between sexes reported in the literature [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adults with HIV have shown lower PhA values compared to those without infection [ 11 ]. The reasons for the lower PhA values in this population are not fully understood, but studies have indicated that a lower PhA is directly associated with increased subcutaneous adipose tissue, and depletion of both muscle mass and body mass [ 9 , 12 ]; Additionally, the literature has shown that factors such as age [ 13 ], sex, body dimensions, biological maturation [ 14 ], physical activity level [ 15 ], and hydration status can directly impact PhA values in different age groups [ 16 ] and in individuals with different health conditions [ 9 ]. Therefore, these factors should be considered in the interpretation of the results found.…”
Section: Introductionmentioning
confidence: 99%
“…The main determinants of PhA are age, sex, and body mass index (BMI) as men and younger individuals might demonstrate higher values in PhA [33][34][35]. Differences in the distribution of body fluids and variations in free-fat mass as well as weight explain the impact of the above-mentioned characteristics on the evaluation of PhA.…”
Section: Bioelectrical Phase Angle: Definition and Characteristicsmentioning
confidence: 99%